Pengaruh Literasi Keuangan, Kecerdasan Spiritual dan Gaya Hidup terhadap Pengelolaan Keuangan Ibu Rumah Tangga - Dimas Perdana Oskar; Rika Wahyuni; Hadi Irfani; Harry Theozard Fikri; Rina Mariana (JURNAL RISET AKUNTANSI JAMBI, 2023)
This research is initiated by the existence of problems faced by housewives in managing finances. Housewives must have basic competencies that must be understood such are planning, management, and financial control activities. Therefore, this study aims to determine the effect of financial literacy, spiritual intelligence and lifestyle on the financial management of housewives simultaneously and partially. This research is quantitative with a survey approach. Data collection used financial literacy questionnaires, spiritual intelligence questionnaires, lifestyle questionnaires, and financial management questionnaires. The sample consisted of 85 housewives in the Lubuk Begalung Subdistrict. Data analysis used is multiple linear regression analysis, F test and t test. This study succeeded in proving simultaneously that financial literacy, spiritual intelligence and lifestyle have a significant effect on the financial management of housewives; partially financial literacy has a significant effect on the financial management of housewives; partially, spiritual intelligence has a significant effect on the financial management of housewives; and partially lifestyle has a significant effect on the financial management of housewives. The contribution of the three variables namely financial literacy, spiritual intelligence and lifestyle to the financial management of housewives is 80,1%.